Intervention strategy with the vaccine candidate Abdala in health workers - Josefa Bell Castillo; María Eugenia García Céspedes; Yoismel Moya Bell (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
The vaccination process against COVID-19 in Cuba is based on epistemological foundations of Medicine and Biomedical Sciences that allowed the execution of clinical trials with nationally produced vaccines, as well as the development of other vaccine candidates during the epidemiological emergency period. The objective of this article is to base the knowledge in relation to the intervention strategy with the vaccine candidate Abdala in Health workers in Santiago de Cuba. Through a bibliographical review carried out from the 1st. From March to May 31st, 2021, scientific articles, data published by the World Health Organization, and textbooks were analyzed, all of which facilitated the recovery and evaluation of systematized information. The intervention strategy with the vaccine candidate Abdala in health workers in Santiago de Cuba demanded a transdisciplinary, intersectoral and participatory management. The application of the procedures of the clinical-epidemiological method revealed the need to amplify an immunization culture with epistemological supports through the systematization of the care process.